2019
DOI: 10.1016/j.semarthrit.2019.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Tocilizumab in giant cell arteritis. Observational, open-label multicenter study of 134 patients in clinical practice

Abstract: Methods: Observational, open-label multicenter study from 40 national referral centers of GCA patients treated with TCZ due to inefficacy or adverse events of previous therapy. Outcomes variables were improvement of clinical features, acute phase reactants, glucocorticoid-sparing effect, prolonged remission and relapses. A comparative study was performed: a) TCZ route (SC vs. IV); b) GCA duration (≤6 vs. >6 months); c) serious infections (with or without); d) ≤15 vs. >15 mg/day at TCZ onset. Results: 134 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
1
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 42 publications
5
51
1
4
Order By: Relevance
“…The risk of serious bacterial infections has been consistently reported to be higher with tocilizumab use for rheumatological diseases. [33][34][35][36] C-reactive protein (CRP) and other acute phase reactants including white blood cell count may be unreliable acute phase reactants and may not rise in response to a secondary bacterial infection after tocilizumab use. 34,37,38 Exactly how long this effect lasts with 1 or 2 doses is unclear.…”
Section: Crp Erythrocyte Sedimentation Rate (Esr)mentioning
confidence: 99%
“…The risk of serious bacterial infections has been consistently reported to be higher with tocilizumab use for rheumatological diseases. [33][34][35][36] C-reactive protein (CRP) and other acute phase reactants including white blood cell count may be unreliable acute phase reactants and may not rise in response to a secondary bacterial infection after tocilizumab use. 34,37,38 Exactly how long this effect lasts with 1 or 2 doses is unclear.…”
Section: Crp Erythrocyte Sedimentation Rate (Esr)mentioning
confidence: 99%
“…BD diagnosis was performed according to the International Study Group for BD (ISGBD) criteria reported in 1990 [17]. As indicated by the Spanish National Guidelines for bDMARDs and tsDMARDs in Rheumatology [18][19][20][21][22], infections as well as malignancies were ruled out before starting the treatment. APR was initiated using dose escalation until reaching a maintenance dose of 30 mg twice daily.…”
Section: Design and Enrollment Criteriamentioning
confidence: 99%
“…Auch unter Alltagsbedingungen bewirkt Tocilizumab nach einem Jahr bei ca. 70 % eine Remission [59]. Allerdings zeigten sich bei diesem Patientenkollektiv, welches vor Therapiebeginn oft intensiv vorbehandelt war, mit ca.…”
Section: Corticosteroideunclassified
“…Allerdings zeigten sich bei diesem Patientenkollektiv, welches vor Therapiebeginn oft intensiv vorbehandelt war, mit ca. 10 Infektionen auf 100 Patientenjahre eine vergleichsweise hohe Infektionsrate [59]. Die Therapie mit Tocilizumab führt nur bei einem Drittel der Patienten zum Rückgang der im MRT nachweisbaren Wandentzündung [60].…”
Section: Corticosteroideunclassified